Obravnava pacientov z adolescentno idiopatsko skoliozo po pristopu SEAS - uvodna raziskava - Naglič, Nada (Rehabilitacija (Ljubljana), 2014)
Background: Scoliosis is a three-dimensional deformity of the spine and trunk, which may deteriorate quickly during periods of rapid growth. A double major curve is scoliosis where both curves are of equal degree of angulation and balance each other. The aim of our pilot study was to examine the effects of treatment according to the Scientific Exercise Approach to Scoliosis (SEAS). Methods: Nine young women with double major scoliosis partici - pated in the study. All of them had five individual exercise sessions according to the SEAS and five exercise sessions in a small group. Functional assessment that included measurements of angle of trunk rotation, hump height, range of motion (ROM) of the spine, and balance was performed at the start of the treatment and 2-8 months after the treatment. Paired t-test was used to compare the mean values of the variables. The obtained p-values were corrected using the false discovery rate (FDR) approach. Statistical significance threshold was set at p = 0.05. Results: The mean age of the participants was 14.8 years (SD 1.9). The mean Cobb angle of the right thoracic curve was 29.6° (SD 9.6°). The mean Cobb angle of the left lumbar curve was 27.3° (SD 10.7°). The mean time between first and second functional assessment was 5 months (SD 2.3). Statistical tests of the data on spine shape, ROM of the spine and balance did not indicate any statistically significant change after the treatment. Conclusions: In order to demonstrate a statistically significant progress of patients with adolescent idiopathic scoliosis treated according to the SEAS, the study should be performed on a larger sample and the number of studied outcomes should be reduced.
Keywords: adolescent idiopathic scoliosis (AIS); adolescentna idiopatska skolioza (AIS); double major curve; dvojna velika krivina; exercises for scoliosis; obseg gibljivosti hrbtenice; Scoliosis; SEAS; spine range of motion; terapevtske vaje za skoliozo